A Numerical Study of Cloud Development Using Silver Iodide Cloud Seeding Module - Zhu, Haoran; Chu, Yongwei; Zhao, Hejue; Ma, Simin; Li, Longyan; Wang, Xueni (Journal of Research in Science and Engineering, 2025)
Based on the IAP-LACS multiple-parameter cloud microphysical scheme which has been coupled into WRF model, Sensitivity tests are designed to study the influence of AgI doses on cloud seeding processes. By coupling the AgI cloud seeding module to the IAP-LACS scheme, the effects of AgI catalyst with different doses on ice crystal formation and precipitation are simulated. The results of ideal sensitivity tests show that, with the increase of the AgI dose, the overall cloud rain show a trend of increasing firstly and decreasing secondly, which corresponds to the fact that appropriate amount of catalyst enhances precipitation while excessive catalyst suppresses precipitation.